Carbon molecular sieve production from defatted spent coffee ground using ZnCl2 and benzene for gas purification. (1st October 2020) - Kaya, M.; Atelge, M.R.; Bekirogullari, M.; Eskicioglu, Cigdem; Atabani, A.E.; Kumar, Gopalakrishnan; Yildiz, Y.S.; Unalan, S.
Graphical abstract: Highlights: The DSCG was used to produce CMS for the first time. The pore diameters of CMS which produced from DSCG are varied from 2 to 4 Å. The produced CMS is suitable for the removal of impurities such as CH4, CO2, NOx. Abstract: The aim of the current study is to manufacture molecular sieve from the defatted spent coffee ground. The defatted spent coffee ground for the specified particle size (100 μm) was chemically activated with different agents (ZnCl2, H3 PO4, KOH) and then carbonized at different temperatures (400–900 °C). A thorough characterization of the produced activated carbon was performed and activated carbons with the highest BET surface area were subsequently used to produce carbon molecular sieve. The surface modification was performed with benzene vapor at different temperatures (600–900 °C) and different combustion times (30–90 min.). In addition to the BET analysis, SEM, TGA and FT-IR analysis were also undertaken. The results obtained through characterizations showed that the pore diameters of carbon molecular sieve produced from defatted spent coffee ground varied from 2 to 4 Å. To conclude, the results suggest that the fabricated carbon molecular sieve can be used for the removal of impurities such as CH4, CO2, NOx and other impurities in natural and biogas considering the porosity of the sieves.